I.x. Notebook containing fragmentary notes made by Kathleen Clarke while writing her memoirs - Clarke, Kathleen, 1878-1972
Clarke's notes and jottings relate to her association with the Fianna Fáil party, her work with the Irish White Cross and Irish Red Cross and her recollections of the various political meetings held in the Mansion House, Dublin. Also included are notes regarding her plans for the organisation of chapters in her memoirs.
Keywords: Clarke, Kathleen, -- 1878-1972; Fianna Fáil; Irish White Cross; Irish Red Cross